Experimental study on the fire resistance of GFRP pultruded tubular columns. (February 2015) - Morgado, T.; Correia, J.R.; Moreira, A.; Branco, F.A.; Tiago, C.
Abstract: This paper presents experimental investigations about the fire behaviour of GFRP pultruded columns with square tubular cross-section. The objectives of the study were to evaluate (i) the efficacy of passive (calcium silicate (CS) boards) and active (water-cooling) systems in providing fire protection to GFRP pultruded columns; and the effects of (ii) the number of sides exposed to fire; and (iii) the service load level on the GFRP columns' fire response. To this end, fire resistance tests were performed on 1.5 m long GFRP columns, subjected to two different load levels corresponding to axial shortenings of L /1500 and L /750 ( L being the span), and simultaneously exposed to fire, in either one or three sides, according to the time–temperature curve defined in ISO 834. Results obtained were analysed regarding the thermal and mechanical responses of the GFRP columns (unprotected and protected), namely in terms of the evolution of axial and transverse displacements, the failure modes and the fire resistance. It was possible to conclude that for one-side exposure, water-cooling is the most effective protection, particularly with flowing water, providing more than 120 min of fire resistance. For three-sides exposure, the fire resistance of the different solutions tested was severely reduced, namely that of the water-cooling systems, which provided fire resistances of only about 20 min, regardless of using flowing water; for this type of exposure, the best performance was provided by the CS board protection, with about 40 min of fire resistance. The results obtained in this study draw the attention to the technical advantages of adopting a building architecture in which the GFRP columns are integrated in the façades and embedded in partition walls, preventing the columns from being exposed to fire in three sides. As expected, the load level increase caused a reduction of fire resistance, due to the higher stresses developed in the sections' walls and to the GFRP strength decrease with temperature.